Study of shear thickening fluid within 3D printed structures - Tan, Jian Da (Nanyang Technological University, 2020)
The study analyses the potential for using shear thickening fluid (STF) within 3D printed structures for sports protective equipment. Effects of the liquid medium and particle concentration of STF on rheology were studied. The STF deemed optimal was polypropylene glycol (PPG), with an average molecular weight of 400, containing 15 wt% of fumed silica, which was used to fill the 3D printed samples. The filament used for 3D printing was a thermoplastic elastomer called Pebax® 3533 SP 01. These samples were cylindrical in shape with either honeycomb or gyroid internal structures. Impact tests on these samples were conducted to compare the differences before and after the addition of STF, whereby results were measured in terms of peak force and energy absorbed from the system. Results demonstrated that the design of the internal structure heavily affected the extent of impact absorption by the STF. The gyroid structure with thicker cell walls experienced the lowest peak force and highest energy absorbed from the system. Implications of the results suggest that STF has a significant potential to be used in sports protective equipment, provided that better internal structures could be designed to fully utilize the STF energy dissipation capabilities. Biggest limitation of this study is the lack of ability to determine the extent of contribution the shear thickening mechanism does to the energy dissipation capabilities.